Respon Pertumbuhan Bibit Ylang-Ylang (Cananga odorata forma genuine) terhadap Pemberian Pupuk Daun di Persemaian - Irdika Mansur; Rahma Sari (Jurnal Silvikultur Tropika, 2021)
Ylang-ylang (Cananga odorata forma genuina) is a plant with high adaptability but the production of ylang-ylang seedlings is still limited and the seeds produced cannot be stored for long time. One of the fertilization techniques on a large scale to optimize plant growth is by using leaf fertilizer. This study aims to analyze the response of ylang-ylang seedlings to the use of two different types of leaf fertilizer at different doses and spraying times. This study used a factorial design with three factors in a completely randomized design. The results showed that the use of different types of leaf fertilizer at certain doses at two different times did not show significant growth. The treatment of 4 g/L water of commercial leaf fertilizer A and 6 g/L water of commercial leaf fertilizer B result to a better influence on the growth of ylang-ylang seedlings.. Keywords: Cananga odorata, completely randomized design, fertilizing, leaf fertilizer, nursery